The Structural Modulation of Amorphous 2D Tungsten Oxide Materials in Magnetron Sputtering - Bo Zhang; Veronika Cicmancova; Benes Ludvik; Stanislav Slang; Petr Kutalek; Martin Motola; Tomas Wagner (Advanced Materials Interfaces)
Abstract 2D oxide materials have gained tremendous attention in the applications. Herein, a synthesis route of 2D WO3 materials via magnetron sputtering is reported. A deposition between 2D monolayers and thin film structure are accomplished according to the temperature of substrate. And 2D monolayers are only formed on a cooled substrate. Ag doping helps to exfoliate 2D WO3 into freestanding monolayers, in which the thickness of 2D monolayer is only ≈3 nm. The ultralarge size of 2D WO3 shows unique features from the traditional 2D material. Resistive switching device and photocatalysis are discussed as examples of application. There is a clear intermediate resistance state in the device with 2D structure. And the failure of resistive switching device is closely related with the 2D structure of WO3. In the application of photocatalysis, an improved two‐step exfoliation, achieving a stack of WO3 monolayers with a large internal volume, is utilized. The enhancements of photocatalysis are obtained with 2D WO3 after exfoliation.